Network : guide to networks - Dean, Tamara. (Course Technology, 2000)
This book covers a wide range of material about networking, from assessments of careers in networking to discussions of local area networks, wide area networks, protocols, topologies, transmission media, and security. It provides a variety of concepts and examinations of the most significant aspects of networking, such as the TCP/IP protocol suite.